All Days 2013
DOI: 10.2118/164341-ms
|View full text |Cite
|
Sign up to set email alerts
|

First EOR Trial using Low Salinity Water Injection in the Greater Burgan Field, Kuwait

Abstract: The Burgan field, the second largest in the world and the largest clastic reservoir, has been in production for 66 years under primary production from natural water drive. The first phase of water injection has just begun in a small part of Burgan as a precursor to peripheral step-in water injection in the topmost Wara reservoir. Tertiary recovery schemes are being evaluated early in the life of this field with the foresight of reaping maximum benefits through early application before waterflood approaches mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…In light of these, low-salinity water injection has become an established EOR method for Endicott field. , Robertson analyzed historical production data from fields that have been waterflooded with about 1000 ppm low-salinity brine and observed that their recoveries were higher than those under high-salinity injection. Patil et al, Vledder et al, Seccombe, Abdulla et al, and Zeinijahromi et al all reported substantial recovery increments ranging from 4–15% oil-in-place. Conversely, less than encouraging field cases have been observed.…”
Section: Discussionmentioning
confidence: 97%
“…In light of these, low-salinity water injection has become an established EOR method for Endicott field. , Robertson analyzed historical production data from fields that have been waterflooded with about 1000 ppm low-salinity brine and observed that their recoveries were higher than those under high-salinity injection. Patil et al, Vledder et al, Seccombe, Abdulla et al, and Zeinijahromi et al all reported substantial recovery increments ranging from 4–15% oil-in-place. Conversely, less than encouraging field cases have been observed.…”
Section: Discussionmentioning
confidence: 97%
“…Low salinity waterflooding projects/field trial/pilots reported in the literature have been dominated by those projects which have been implemented in sandstone reservoirs. Researchers (McGuire et al 2005;Eric Robertson 2007;Skrettingland et al 2011;Abdulla et al 2013a;Erke et al 2016;Al Qattan et al 2018;Katende and Sagala 2019) have reported field implantation of low salinity waterflooding in sandstone reservoirs. On the other hand, studies which discuss low salinity projects in carbonates are scarce.…”
Section: Field Implementation Of Low Salinity Waterflood In Carbonatesmentioning
confidence: 99%
“…In addition, the low content of organic acid in the Snorre oil ensured that the reservoir was already close to optimum wetting conditions, such that low saline water could not significantly improve recovery [36]. Furthermore, Abdulla et al [225] documented two recent SWCT tests conducted in the giant Kuwait Burgan oilfield. The tests were implemented in two reservoir formations with the least clay content and good quality rock.…”
Section: Sandstone Reservoirsmentioning
confidence: 99%